Differential Binding of Mitochondrial Transcripts by MRB8170 and MRB4160 Regulates Distinct Editing Fates of Mitochondrial mRNA in Trypanosomes - Dixit, Sameer; Müller-McNicoll, Michaela; David, Vojtěch; Zarnack, Kathi; Ule, Jernej; Hashimi, Hassan; Lukeš, Julius (mBio, 2017)
UNLABELLED: A dozen mRNAs are edited by multiple insertions and/or deletions of uridine residues in the mitochondrion of Trypanosoma brucei Several protein complexes have been implicated in performing this type of RNA editing, including the mitochondrial RNA-binding complex 1 (MRB1). Two paralogous novel RNA-binding proteins, MRB8170 and MRB4160, are loosely associated with the core MRB1 complex. Their roles in RNA editing and effects on target mRNAs are so far not well understood. In this study, individual-nucleotide-resolution UV-cross-linking and affinity purification (iCLAP) revealed a preferential binding of both proteins to mitochondrial mRNAs, which was positively correlated with their extent of editing. Integrating additional in vivo and in vitro data, we propose that binding of MRB8170 and/or MRB4160 onto pre-mRNA marks it for the initiation of editing and that initial binding of both proteins may facilitate the recruitment of other components of the RNA editing/processing machinery to ensure efficient editing. Surprisingly, MRB8170 also binds never-edited mRNAs, suggesting that at least this paralog has an additional role outside RNA editing to shape the mitochondrial transcriptome. IMPORTANCE: Trypanosoma brucei mitochondrial mRNAs undergo maturation by RNA editing, a unique process involving decrypting open reading frames by the precise deletion and/or insertion of uridine (U) residues at specific positions on an mRNA. This process is catalyzed by multiprotein complexes, such as the RNA editing core complex, which provides the enzymatic activities needed for U insertion/deletion at a single editing site. Less well understood is how RNA editing occurs throughout an mRNA bearing multiple sites. To address this question, we mapped at single-nucleotide resolution the RNA interactions of two unique RNA-binding proteins (RBPs). These RBPs are part of the mitochondrial RNA-binding complex 1, hypothesized to mediate multiple rounds of RNA editing. Both RBPs were shown to mark mRNAs for the process in correlation with the number of editing sites on the transcript. Surprisingly, one also binds mRNAs that bypass RNA editing, indicating that it may have an additional role outside RNA editing.
Keywords: vazba proteinů; RNA Precursors; RNA Editing; Protozoan Proteins; mitochondrie; editace RNA; Mitochondria; Protein Binding; Trypanosoma brucei brucei; prekurzory RNA; protozoální proteiny